Analisis Hukum Pelaksanaan Arisan Online Menurut Hukum Perdata : (Studi Kasus Putusan Pengadilan Negeri Banjarmasin Nomor 99/PDT.G/2017/PN.Bjm) - Lale Dinda Mutiara Santi; Sahruddin Sahruddin (Private Law, 2023)
The purpose of this study is to determine the basis of the judge's considerations and the legal consequences in Decision Number 99/Pdt.G/2017/PN.Bjm. The results of this study are (1) The legal consequences of the agreement made by the parties implementing the online credit association (arisan), namely the emergence of rights and obligations between the defendant and the plaintiff, the defendant has the right to get money from the online credit association slot payment, and the obligation of the plaintiff is to deposit the online social gathering money to the defendant. (2) The basis of the judge's consideration in deciding case Number 99/Pdt.G/2017/PN.Bjm is form of a photocopy of the receipt of the online credit association (arisan) payment. The judge considered the case based on articles 1338, 1238, and 1239 of the Civil Code and decided to grant partially the plaintiff's claim with verstek (article 149 Rbg).